Cobalt(II) complexes of α-diimine derived from cycloalkylamines as controlling agents for organometallic mediated radical polymerization of vinyl acetate - Riga, Beatriz A. [UNESP]; Silva, Yan F. [UNESP]; Nascimento, Otaciro R.; Machado, Antonio E.H.; Carvalho-Jr, Valdemiro P. [UNESP]; Goi, Beatriz E. [UNESP] (My University, 2020)
A series of cobalt(II)-α-diimine complexes derived from cycloalkylamines (cycloalkyl = cyclopentyl (1a), cyclohexyl (1b), cycloheptyl (1c), and cyclooctyl (1d)) were synthesized: [CoCl2(Pent-DAB)] (2a), [CoCl2(Hex-DAB)] (2b), [CoCl2(Hept-DAB)] (2c), and [CoCl2(Oct-DAB)] (2d). The α-diimines 1a-d were characterized by FTIR, UV–Vis, and 1H- and 13C NMR spectroscopy, while their respective cobalt(II) complexes (2a-d) were characterized by elemental analysis, FTIR, UV–Vis, EPR, and computational studies. The ability of complexes 2a-d to mediate the vinyl acetate (VAc) polymerization initiated by AIBN, according to a cobalt-mediated radical polymerization (CMRP) mechanism, was explored. A mechanistic investigation of radical trapping based on the combination of theoretical and experimental results for CMRP using 2a-d was conducted. This study shows that the activation/deactivation equilibrium exerted by 2a-d occurs by only one of the faces of the complexes via reversible-termination mechanism. The molecular weight increased in direct proportion to the monomer conversion in the early stages of polymerization for complexes 2a and 2b, while uncontrolled polymerization was observed for 2c and 2d. The molecular weights indicate that the steric effect operated by the cycloalkyl substituents plays an important role in the polymerization control, and that a greater steric hindrance disfavors the dormant state for CMRP equilibrium.
Keywords: CMRP; Controlled radical polymerization; Organometallic; Transition metal; Vinyl acetate